Čustveno soočanje s posledicami življenjsko ogrožajočih zdravstvenih stanj - Simonič, Barbara (Obzornik zdravstvene nege, 2024)
Introduction: Experiencing and surviving an acute life-threatening medical condition is a highly stressful (traumatic) event that significantly impacts on the life of an individual and his or her relatives. The purpose of the study was therefore to examine the relationship between the experiencing an acute life-threatening health condition and emotional coping.Methods: A descriptive and correlation cross-sectional study was conducted on participants with experience of acute life-threatening health condition (n=54) and relatives (n=59). Results: Emotional processing as a way of coping is positively correlated with better life functioning (r = 0.455, p < 0.01), post-traumatic growth (r = 0.341, p < 0.01) and the experience of individual strengths (r = 0.337, p < 0.01). Emotion expressing as a way of coping is positively correlated with better life functioning (r = 0.416, p < 0.01), post-traumatic growth (r = 0.252, p < 0.05) and experiencing individual strengths (r = 0.481, p < 0.01). Emotional coping in patients is explained by gender (ß = –0,51). Emotional coping in relatives was explained by post-traumatic growth (ß = 0,41) and individual strengths (ß = 0,51).Discussion and conclusion: Emotional coping with the consequences of an acute life-threatening health condition plays an important role in post-traumatic growth, greater sense of life success, individual strengths, connection with others and spiritual change, on the other hand it is associated with less marked symptoms of depression, anxiety, and stress. Adequate emotional coping with stress while experiencing and surviving a life-threatening health condition is thus crucial in successfully adjusting to life after this event.
Keywords: blagostanje; čustveno spoprijemanje; duševno zdravje; emotional coping; life functionality; mental health; posttraumatic growth; posttravmatska rast; well-being; življenjska funkcionalnost